Using Gatekeeper Training as a CVE Tool: Replication and Evaluation of a Gatekeeper Program in Prince George's County, Maryland, United States, 2019 - McGee, Sibel ([Verlag nicht ermittelbar], 2020)
This study evaluated Global Citizen's Forum (GCF), an afterschool youth program designed as a peer gatekeeping program in the area of violent extremism. GCF was implemented in two private high schools in Maryland during spring of 2019. Although the study was designed as a quasi-experimental research with pre/post testing of treatment and control groups, implementation challenges resulted in design problems and a small sample, allowing only for exploratory study. The preliminary results suggest that GCF is associated with some statistically significant gains in participants' knowledge and attitude. The study also presents team's qualitative findings as well as GCF replication framework and financial cost analysis. An assessment of the GCF implementation experience and related observations indicates that GCF may be difficult to replicate due to community sensitivities about accepting the violent extremism threat and the ability of service providers to teach the GCF curriculum. For conclusive and reliable results, this study needs to be replicated with participation of a larger sample.